Contextualizing code-switching: testing the effects of reggaetón labels and listening frequency in an Acceptability Judgment Task - Callesano, Salvatore; Delgado, Rodrigo; Ma, Wenyue; Trybulec, Erin; Reyes, Gabriella (Frontiers in Communication, 2025)
This study presents an Acceptability Judgment Task (AJT) conducted with Latinx1 Spanish-English bilinguals in the United States. We take a social approach to the AJT by contextualizing code-switching (CS) within the context of reggaetón music by adding experimental labels to sentences and examine how the results vary according to enjoyment and frequency of listening to reggaetón music. Results from mixed-effects regression models show effects of sentence grammaticality and frequency of listening to reggaetón. Results do not show effects of the reggaetón label on the CS sentences, however we find higher ratings for ungrammatical sentences and lower ratings for grammatical sentences than previously shown in the AJT literature. This study highlights the importance of the social context of code-switching when investigating acceptability judgments.